Rehabilitating ailing Malaysia companies using the new corporate rescue mechanism / Norziana Lokman, Julizaerma Mohamed Khudzairi and Sarina Othman - Lokman, Norziana; Mohamed Khudzairi, Julizaerma; Othman, Sarina (Universiti Teknologi MARA, 2020)
This paper focuses on the Malaysia Corporate Rescue Mechanism 2016, which is a relatively new rescue mechanism to the Malaysian corporate environment. The Companies Commission of Malaysia introduces the mechanism as part of the insolvency framework to help small companies facing financial difficulties to be rehabilitated. There are two options available for owners of small companies to rescue their companies’ businesses. The first option is corporate voluntary arrangement (CVA), and the second option is judicial management (JM). This paper has two main objectives: (i) to outline the characteristics of CVA and JM; and (ii) to identify and analyse the weaknesses of the revised corporate rescue schemes. This paper is a perspective, opinion and commentary article on the recent implementation of corporate rescue mechanism.